2018
DOI: 10.1016/j.bpj.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Unfolding of Titin I27 Single and Bi Domain with High-Pressure NMR Spectroscopy

Abstract: A complete description of the pathways and mechanisms of protein folding requires a detailed structural and energetic characterization of the folding energy landscape. Simulations, when corroborated by experimental data yielding global information on the folding process, can provide this level of insight. Molecular dynamics (MD) has often been combined with force spectroscopy experiments to decipher the unfolding mechanism of titin immunoglobulin-like single or multidomain, the giant multimodular protein from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…From the analysis of the residue-specific denaturation curves, the first event in DEN4-ED3 unfolding was found to be the rupture of the junction between the N-and C-terminal ß-strands 1 and 9, on one edge of the ß-sandwich. Interestingly, this behavior is rather similar to what has been recently shown for the I27 domain of the multimodular giant protein Titin from the striated muscle cell, which also adopts an Ig-like fold, but with a significantly different sequence (sequence identity <7%) [27]. In Titin I27, the N-and C-termini are involved in ß-sheet structures: a small, distorted antiparallel (AB) ß-sheet, and a longer parallel (A'G) ß-sheet (where the capital letters stand for the ß-strands numbering, following the usual convention for Ig-like modules).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…From the analysis of the residue-specific denaturation curves, the first event in DEN4-ED3 unfolding was found to be the rupture of the junction between the N-and C-terminal ß-strands 1 and 9, on one edge of the ß-sandwich. Interestingly, this behavior is rather similar to what has been recently shown for the I27 domain of the multimodular giant protein Titin from the striated muscle cell, which also adopts an Ig-like fold, but with a significantly different sequence (sequence identity <7%) [27]. In Titin I27, the N-and C-termini are involved in ß-sheet structures: a small, distorted antiparallel (AB) ß-sheet, and a longer parallel (A'G) ß-sheet (where the capital letters stand for the ß-strands numbering, following the usual convention for Ig-like modules).…”
Section: Discussionsupporting
confidence: 82%
“…Besides, our P-jump experiments yield a value of k f 0 = 1.14 (± 0.08) × 10 −3 s −1 for the rate constant for folding of DEN4-ED3, more than one order of magnitude lower than the value previously measured for Titin I27 (k f 0 = 2.24 (± 0.11) × 10 −2 s −1 ) [27]. This seems to corroborate the observation made by Clarke et al [32], who found a positive linear correlation between the logarithm of the rate constant for folding and the stability of Ig-like protein.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations